Bile Cast Nephropathy an Important Biliary Culprit of Kidney Injury. Issue 2 (4th March 2021) - Yusuf, Fouzia; Weissman, Simcha; Qureshi, Nabeel; Ibrahim, Mounir; Kurtz, Daniel; Manandhar, Lochana; Sciarra, Michael; Elias, Sameh
ABSTRACT: Bile cast nephropathy (BCN) is a rare form of acute kidney injury (AKI) that occurs in the setting of hyperbilirubinemia. We present the case of a 67 year-old male with severe kidney injury who was found to have obstructive cholestasis. By way of this report, we aim to expand upon the existing literature and showcase the importance of timely endoscopic retrograde cholangio-pancreatography (ERCP) in this setting, in order to prevent irreversible kidney damage.